2022
DOI: 10.3390/life12122018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Pregnancy Overweight/Obesity on the Pattern of Association of Hypertension Susceptibility Genes with Preeclampsia

Abstract: The aim of this study was to explore the effects of pre-pregnancy overweight/obesity on the pattern of association of hypertension susceptibility genes with preeclampsia (PE). Ten single-nucleotide polymorphisms (SNPs) of the 10 genome-wide association studies (GWAS)-significant hypertension/blood pressure (BP) candidate genes were genotyped in 950 pregnant women divided into two cohorts according to their pre-pregnancy body mass index (preBMI): preBMI ≥ 25 (162 with PE and 159 control) and preBMI < 25 (290… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Concurrently, there are some discrepancies in the results of these studies: SNP BAG6 rs805303 G > A has a protective value for HTN in men (not in women!) (OR = 0.30), but in parallel, this polymorphism marks a low risk of developing pre-eclampsia in pregnant women as a whole (OR = 0.55-0.78) [104] and among women with a BMI ≥ 25 (OR = 0.36-0.66) [105]. One of the possible reasons for these sex-specific differences in the value of the BAG6 rs805303 G > A locus in the development of pathology with elevated BP may be the modifying effect on the phenotypic manifestation of this polymorphism of an unequal confounder factor list taken into account in these studies (BMI, TC, TG, HDL-C, LDL-C, blood glucose, smokers-present study; age, family history of PE, pre-pregnancy BMI, obesity, number of gravidities, spontaneous/induced abortions, stillbirths, smokers-previous study [104]).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Concurrently, there are some discrepancies in the results of these studies: SNP BAG6 rs805303 G > A has a protective value for HTN in men (not in women!) (OR = 0.30), but in parallel, this polymorphism marks a low risk of developing pre-eclampsia in pregnant women as a whole (OR = 0.55-0.78) [104] and among women with a BMI ≥ 25 (OR = 0.36-0.66) [105]. One of the possible reasons for these sex-specific differences in the value of the BAG6 rs805303 G > A locus in the development of pathology with elevated BP may be the modifying effect on the phenotypic manifestation of this polymorphism of an unequal confounder factor list taken into account in these studies (BMI, TC, TG, HDL-C, LDL-C, blood glucose, smokers-present study; age, family history of PE, pre-pregnancy BMI, obesity, number of gravidities, spontaneous/induced abortions, stillbirths, smokers-previous study [104]).…”
Section: Discussionmentioning
confidence: 92%
“…It is quite interesting that the data of this work are largely consistent with our previously published materials in which, during an associative study of a women sample with pre-eclampsia/without pre-eclampsia from the identical population of Europeans in Central Russia (the list of studied loci was analogous), it was found that the HFE rs1799945 C > G increased the pre-eclampsia risk (for allele G OR = 2.24) and BAG6 rs805303 G > A decreased the pre-eclampsia risk (for allele A OR = 0.55-0.78) [104] including this pregnancy complication risk in women with BMI ≥ 25 (for allele A OR = 0.36-0.66) [105]. So, the polymorphic variant G rs1799945 HFE increases both the HTN risk in women (data from this work, OR = 11.15 for genotype GG) and the pre-eclampsia risk in women (a specific symptom of this complication of pregnancy is increased BP (OR= 2.24 [104])), which may indicate the "universality" of this genetic marker as a risk factor for the development of hypertensive conditions in European women in Central Russia, and allows us to recommend its use in practical medicine in order to distinguish women with a high risk of developing elevated BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants of present research have previously been involved in other genetic studies of disorders/outcomes of pregnancy (newborn weight, preeclampsia, FGR) (detailed data on the results of these studies are contained in previous publications [ 40 , 75 , 76 , 78 , 79 , 80 , 81 , 82 ]). Table 1 presents the biological/medical characteristics of the FGR/FGR free cohorts formed.…”
Section: Methodsmentioning
confidence: 99%
“…The probable KOA effector SNPs/genes (taking into account proxy SNPs, r 2 ≥ 0.80 [ 60 , 61 ]) have been chosen for their functionality (the in silico approach was applied [ 62 , 63 ] based on online integrated resources of bioinformatics information [ 64 , 65 , 66 ] including the GTEx [ 67 ], PolyPhen2 [ 68 ], HaploReg [ 39 ], Blood eQTL [ 69 ], SIFT [ 70 ], GeneMANIA [ 71 ]).…”
Section: Methodsmentioning
confidence: 99%